Resistance to irradiation of micro-algae growing in the storage pools of a nuclear reactor investigated by NMR and neutron spectroscopies. Issue 3 (2010) - Rivasseau Rivasseau, Corinne Corinne; Farhi Farhi, Emmanuel Emmanuel; Gromova Gromova, Marina Marina; Ollivier Ollivier, Jacques Jacques; Bligny Bligny, Richard Richard
Abstract : A green Chlorophycean micro-alga surviving high irradiation doses has been discovered in the storage pools of a nuclear reactor. Investigating the mechanisms sustaining its properties is of peculiar interest. Metabolic impact of irradiation on the micro-alga as well as structural macromolecular impact were investigated using nuclear magnetic resonance and neutron backscattering spectroscopy. Carbohydrate, amino acid and organic acid content studied as a function of the irradiation dose revealed an intense protein repair activity. Resilience was extracted according to irradiation dose and compared to that of other extremophile species.